1990
DOI: 10.1002/bdd.2510110908
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of a pharmacological dose of vitamin D3 from two different lipid vehicles in man: Comparison of peanut oil and a medium chain triglyceride

Abstract: The absorption of a pharmacological dose of vitamin D, from two different lipid vehicles, peanut oil, containing long chain fatty acids, and a medium chain triglyceride was compared. Serial measurements of the serum concentration of vitamin D, after dosage were made. The serum levels of 25-hydroxyvitamin D,, the major circulating vitamin D3 metabolite, were also determined. The analytical methods used were based on HPLC. In the fasting state, the serum levels of vitamin D, were significantly higher after admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 26 publications
1
21
0
1
Order By: Relevance
“…On first examination, the data appear contradictory and some reveal better performance for MCT 21,22 whilst others suggest a preference for LCT 13,[23][24][25] (see Ref. 14 for a review). However, closer examination reveals that the two studies performed using either fasted healthy humans or dogs 13,24,25 showed, in agreement with our results, higher drug exposure after administration of poorly water-soluble compounds in LCT solution formulations. All the other studies (including all those where MCT was shown to be most preferable) were conducted in rats.…”
Section: Lipid Solution Formulations (Study 1)mentioning
confidence: 93%
“…On first examination, the data appear contradictory and some reveal better performance for MCT 21,22 whilst others suggest a preference for LCT 13,[23][24][25] (see Ref. 14 for a review). However, closer examination reveals that the two studies performed using either fasted healthy humans or dogs 13,24,25 showed, in agreement with our results, higher drug exposure after administration of poorly water-soluble compounds in LCT solution formulations. All the other studies (including all those where MCT was shown to be most preferable) were conducted in rats.…”
Section: Lipid Solution Formulations (Study 1)mentioning
confidence: 93%
“…Long-chain fatty acids and their glycerides are well known to be transported to the lymphatic system after absorbed from the small intestine (29). It was also reported that lipids with long-chain fatty acids promote the transport of drugs into the lymphatic system more effectively than those with short-and/or medium-chain fatty acids (15)(16)(17). Furthermore, SNEDDS/SMEDDS formulations composed of lipids with long-chain fatty acids were reported to result in the lymphatic transport of larger amount of drugs than those with medium-chain fatty acids (30,31).…”
Section: Preparation Of Lc-snedds Formulationmentioning
confidence: 97%
“…Since the ratio of lymphatic transport of drugs was reported to be de pendent on the nature of oils used (15)(16)(17)30,31,37), the ratios were also independently defined as a F and a B for LC-SNEDDS F and MC-SNEDDS B, respectively. In the case of N-251, Fa can be assumed to be unity because N-251 was considered to be almost completely absorbed as described above.…”
Section: Simulation Of Quantitative Contribution Of Lymphatic Transpomentioning
confidence: 99%
See 1 more Smart Citation
“…Ácidos graxos de cadeia longa provenientes do óleo de amendoim facilitaram a absorção de vitamina D presente, quando comparada a doses farmacológicas dessa vitamina 29 .…”
Section: B I O D I S P O N I B I L I D a D E D A V I T A M I N A Dunclassified